Speech Act Theory in Visual Narratives: An Analysis of Communication through Sequential Art - Chattopadhyay, Pallabi (Gipan, 2024)
An increasing curiosity in communication through visual narratives has been observed in recent years in multidisciplinary research. This paper focuses on how speech act theory plays a role in visual linguistics through the analysis of a few selected visual narratives. With the help of a content analysis methodology, this paper focuses on qualitative research by analysing the data through the speech act theory present in the visual narratives. It demonstrates its intent through a few carefully chosen visual narratives, ‘Hada Bhoda’ Accepted: 20 June 2024 Orcid https://orcid.org/0009-0006-5771-6941 Cite Chattopadhyay, P. (2024). Speech act theory in visual narratives: An analysis of communication through sequential art. Gipan, 6(1), 119–133. https://doi.org/10.3126/gipan.v6i1. ...... Introduction and ‘Doraemon’ from two different cultures, Bengali and Japanese respectively. The study indicates how picture stories serve as a type of speaking act, transmitting meaning in the conversations present in the visual narratives and also prompting responses from viewers. It is possible to have a greater knowledge of the communication dynamics, intentionality, and impacts of language and speech within the visual narratives by analysing locutionary, illocutionary and perlocutionary acts in the picture stories.